A limitação temporal expressa do precedente judicial em períodos de excecionalidade. - Freitas, Fellipe Domingues de Barros (2023)
The purpose of the present work is to verify if there is a theoretical and dogmatic foundation capable of supporting the construction of a precedent limited in time to an exceptional circumstance. This is because in the face of a culture of singular judgments without extracting a ratio decidendi with clarity and consistency, it becomes even more necessary to use tools that contribute to legal certainty. Throughout the work, it was verified through the literature review on the subject, that the elements of overcoming and distinguishing the judicial precedent would be insufficient to contribute to the stability, coherence and integrity of the system advocated by art. 927 of the CPC in an atypical situation of exceptionality. It was found that a formalistic and binding rigor would be necessary in order to avoid contradictory decisions based on principles that would reduce arbitrariness, such as a vote that occurred in the judgment of ADI 6363. The conclusion demonstrates the existence of necessary requirements to encompass the possibility of building a precedent limited to the exceptional event and that it is possible to apply it to other situations of similar abnormalities.